Glucocorticoid regulation of cancer development and progression - Khadka, Stuti; Druffner, Sara R.; Duncan, Benjamin C.; Busada, Jonathan T. (Frontiers in Endocrinology, 2023)
Glucocorticoids are steroid hormones that regulate a host of cellular and physiological functions. However, they are arguably best known for their potent anti-inflammatory properties. Chronic inflammation is well-known to promote the development and progression of numerous types of cancer, and emerging evidence suggests that glucocorticoid regulation of inflammation affects cancer development. However, the timing, intensity, and duration of glucocorticoid signaling have important but often contradictory effects on cancer development. Moreover, glucocorticoids are widely used in parallel with radiation and chemotherapy to control pain, dyspnea, and swelling, but their use may compromise anti-tumor immunity. This review will explore the effects of glucocorticoids on cancer development and progression with particular focus on pro and anti-tumor immunity.